Investment Marketing Communication in Attracting Investors to DPMPTSP - Setiyawan, Didik; Harliantara, Harliantara; Nurannafi Farni Syam Maella (PT. Gudang Pustaka Cendekia, 2025)
This study evaluates the effectiveness of the East Java Province DPMPTSP marketing communication strategy in investment promotion in 2023, focusing on the marketing mix elements: product, price, place, and promotion. Through a qualitative approach, this study analyzes promotional activities that include the development of promotional materials, expansion of international networks, and strengthening of regional branding. The results of the study indicate that innovative efforts in developing promotional materials using the latest technology and interactive approaches have been carried out. However, an in-depth evaluation is needed to ensure the effectiveness of promotional materials in meeting investor needs. Price transparency, although not explicitly focused on, is important for investment decisions. This study recommends improving information related to investment costs and incentives. International cooperation, such as with the State of Neuvo Leon-Mexico, shows efforts to expand investment networks and global market visibility, with an evaluation of the benefits and costs required. Promotional activities such as seminars on investment strategies focus on strengthening regional branding and effective promotional techniques. The novelty of this study lies in the comprehensive analysis of marketing mix elements in the context of investment promotion as well as recommendations for continuous adaptation according to market changes. These findings provide new insights for the development of more effective investment marketing communication strategies in the future.